Dynamic control of hybrid grafted perfect vector vortex beams - Ahmed, Hammad; Ansari, Muhammad Afnan; Li, Yan; Zentgraf, Thomas; Mehmood, Muhammad Qasim; Chen, Xianzhong (Nature Communications)
Perfect vector vortex beams (PVVBs) have attracted considerable interest due to their peculiar optical features. PVVBs are typically generated through the superposition of perfect vortex beams, which suffer from the limited number of topological charges (TCs). Furthermore, dynamic control of PVVBs is desirable and has not been reported. We propose and experimentally demonstrate hybrid grafted perfect vector vortex beams (GPVVBs) and their dynamic control. Hybrid GPVVBs are generated through the superposition of grafted perfect vortex beams with a multifunctional metasurface. The generated hybrid GPVVBs possess spatially variant rates of polarization change due to the involvement of more TCs. Each hybrid GPVVB includes different GPVVBs in the same beam, adding more design flexibility. Moreover, these beams are dynamically controlled with a rotating half waveplate. The generated dynamic GPVVBs may find applications in the fields where dynamic control is in high demand, including optical encryption, dense data communication, and multiple particle manipulation.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Demonstration of Hong-Ou-Mandel interference in an LNOI directional coupler - Babel, Silia; Bollmers, Laura; Massaro, Marcello; Luo, Kai Hong; Stefszky, Michael; Pegoraro, Federico; Held, Philip; Herrmann, Harald; Eigner, Christof; Brecht, Benjamin; Padberg, Laura; Silberhorn, Christine (Optics Express)
Interference between single photons is key for many quantum optics experiments and applications in quantum technologies, such as quantum communication or computation. It is advantageous to operate the systems at telecommunication wavelengths and to integrate the setups for these applications in order to improve stability, compactness and scalability. A new promising material platform for integrated quantum optics is lithium niobate on insulator (LNOI). Here, we realise Hong-Ou-Mandel (HOM) interference between telecom photons from an engineered parametric down-conversion source in an LNOI directional coupler. The coupler has been designed and fabricated in house and provides close to perfect balanced beam splitting. We obtain a raw HOM visibility of (93.5 ± 0.7) %, limited mainly by the source performance and in good agreement with off-chip measurements. This lays the foundation for more sophisticated quantum experiments in LNOI.
Keywords: Atomic and Molecular Physics; and Optics

The Optimal Depth of Variational Quantum Algorithms Is QCMA-Hard to Approximate - Bittel, Lennart; Gharibian, Sevag; Kliesch, Martin (Proceedings of the 38th Computational Complexity Conference (CCC))
Variational Quantum Algorithms (VQAs), such as the Quantum Approximate Optimization Algorithm (QAOA) of [Farhi, Goldstone, Gutmann, 2014], have seen intense study towards near-term applications on quantum hardware. A crucial parameter for VQAs is the depth of the variational ansatz used - the smaller the depth, the more amenable the ansatz is to near-term quantum hardware in that it gives the circuit a chance to be fully executed before the system decoheres. This potential for depth reduction has made VQAs a staple of Noisy Intermediate-Scale Quantum (NISQ)-era research. In this work, we show that approximating the optimal depth for a given VQA ansatz is intractable. Formally, we show that for any constant $ε>0$, it is QCMA-hard to approximate the optimal depth of a VQA ansatz within multiplicative factor $N^{1-ε}$, for $N$ denoting the encoding size of the VQA instance. (Here, Quantum Classical Merlin-Arthur (QCMA) is a quantum generalization of NP.) We then show that this hardness persists even in the "simpler" setting of QAOAs. To our knowledge, this yields the first natural QCMA-hard-to-approximate problems. To achieve these results, we bypass the need for a PCP theorem for QCMA by appealing to the disperser-based NP-hardness of approximation construction of [Umans, FOCS 1999].

Coherent driving of direct and indirect excitons in a quantum dot molecule - Bopp, Frederik; Schall, Johannes; Bart, Nikolai; Vögl, Florian; Cullip, Charlotte; Sbresny, Friedrich; Boos, Katarina; Thalacker, Christopher; Lienhart, Michelle; Rodt, Sven; Reuter, Dirk; Ludwig, Arne; et al. (Physical Review B)

Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Fully guided and phase locked Ti:PPLN waveguide squeezing for applications in quantum sensing - Domeneguetti, Renato; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas S.; Gehring, Tobias (Optics Letters)
This work reports a fully guided setup for single-mode squeezing on integrated titanium-indiffused periodically poled nonlinear resonators. A continuous-wave laser beam is delivered and the squeezed field is collected by single-mode fibers; up to −3.17(9) dB of useful squeezing is available in fibers. To showcase the usefulness of such a fiber-coupled device, we applied the generated squeezed light in a fiber-based phase sensing experiment, showing a quantum enhancement in the signal-to-noise ratio of 0.35 dB. Moreover, our investigation of the effect of photorefraction on the cavity resonance condition suggests that it causes system instabilities at high powers.
Keywords: Atomic and Molecular Physics; and Optics

SIMULATeQCD: A simple multi-GPU lattice code for QCD calculations - Mazur, Lukas; Bollweg, Dennis; Clarke, David A.; Altenkort, Luis; Kaczmarek, Olaf; Larsen, Rasmus; Shu, Hai-Tao; Goswami, Jishnu; Scior, Philipp; Sandmeyer, Hauke; Neumann, Marius; Dick, Henrik; et al. (Computer Physics Communications)
The rise of exascale supercomputers has fueled competition among GPU vendors, driving lattice QCD developers to write code that supports multiple APIs. Moreover, new developments in algorithms and physics research require frequent updates to existing software. These challenges have to be balanced against constantly changing personnel. At the same time, there is a wide range of applications for HISQ fermions in QCD studies. This situation encourages the development of software featuring a HISQ action that is flexible, high-performing, open source, easy to use, and easy to adapt. In this technical paper, we explain the design strategy, provide implementation details, list available algorithms and modules, and show key performance indicators for SIMULATeQCD, a simple multi-GPU lattice code for large-scale QCD calculations, mainly developed and used by the HotQCD collaboration. The code is publicly available on GitHub.

Viscosity of pure-glue QCD from the lattice - Altenkort, Luis; Eller, Alexander M.; Francis, Anthony; Kaczmarek, Olaf; Mazur, Lukas; Moore, Guy D.; Shu, Hai-Tao (Physical Review D)

Multi-FPGA Designs and Scaling of HPC Challenge Benchmarks via MPI and Circuit-Switched Inter-FPGA Networks - Meyer, Marius; Kenter, Tobias; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems)
While FPGA accelerator boards and their respective high-level design tools are maturing, there is still a lack of multi-FPGA applications, libraries, and not least, benchmarks and reference implementations towards sustained HPC usage of these devices. As in the early days of GPUs in HPC, for workloads that can reasonably be decoupled into loosely coupled working sets, multi-accelerator support can be achieved by using standard communication interfaces like MPI on the host side. However, for performance and productivity, some applications can profit from a tighter coupling of the accelerators. FPGAs offer unique opportunities here when extending the dataflow characteristics to their communication interfaces. In this work, we extend the HPCC FPGA benchmark suite by multi-FPGA support and three missing benchmarks that particularly characterize or stress inter-device communication: b_eff, PTRANS, and LINPACK. With all benchmarks implemented for current boards with Intel and Xilinx FPGAs, we established a baseline for multi-FPGA performance. Additionally, for the communication-centric benchmarks, we explored the potential of direct FPGA-to-FPGA communication with a circuit-switched inter-FPGA network that is currently only available for one of the boards. The evaluation with parallel execution on up to 26 FPGA boards makes use of one of the largest academic FPGA installations.
Keywords: General Computer Science

Computing and Compressing Electron Repulsion Integrals on FPGAs - Wu, Xin; Kenter, Tobias; Schade, Robert; Kühne, Thomas; Plessl, Christian (2023 IEEE 31st Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))
The computation of electron repulsion integrals (ERIs) over Gaussian-type orbitals (GTOs) is a challenging problem in quantum-mechanics-based atomistic simulations. In practical simulations, several trillions of ERIs may have to be computed for every time step. In this work, we investigate FPGAs as accelerators for the ERI computation. We use template parameters, here within the Intel oneAPI tool flow, to create customized designs for 256 different ERI quartet classes, based on their orbitals. To maximize data reuse, all intermediates are buffered in FPGA on-chip memory with customized layout. The pre-calculation of intermediates also helps to overcome data dependencies caused by multi-dimensional recurrence relations. The involved loop structures are partially or even fully unrolled for high throughput of FPGA kernels. Furthermore, a lossy compression algorithm utilizing arbitrary bitwidth integers is integrated in the FPGA kernels. To our best knowledge, this is the first work on ERI computation on FPGAs that supports more than just the single most basic quartet class. Also, the integration of ERI computation and compression it a novelty that is not even covered by CPU or GPU libraries so far. Our evaluation shows that using 16-bit integer for the ERI compression, the fastest FPGA kernels exceed the performance of 10 GERIS ($10 × 10^9$ ERIs per second) on one Intel Stratix 10 GX 2800 FPGA, with maximum absolute errors around $10^{-7}$ - $10^{-5}$ Hartree. The measured throughput can be accurately explained by a performance model. The FPGA kernels deployed on 2 FPGAs outperform similar computations using the widely used libint reference on a two-socket server with 40 Xeon Gold 6148 CPU cores of the same process technology by factors up to 6.0x and on a new two-socket server with 128 EPYC 7713 CPU cores by up to 1.9x.

Breaking the exascale barrier for the electronic structure problem in ab-initio molecular dynamics - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Kühne, Thomas; Plessl, Christian (The International Journal of High Performance Computing Applications)
The non-orthogonal local submatrix method applied to electronic structure–based molecular dynamics simulations is shown to exceed 1.1 EFLOP/s in FP16/FP32-mixed floating-point arithmetic when using 4400 NVIDIA A100 GPUs of the Perlmutter system. This is enabled by a modification of the original method that pushes the sustained fraction of the peak performance to about 80%. Example calculations are performed for SARS-CoV-2 spike proteins with up to 83 million atoms.
Keywords: Hardware and Architecture; Theoretical Computer Science; Software

Modeling of Masked Droplet Deposition for Site-Controlled Ga Droplets - Feddersen, Stefan; Zolatanosha, Viktoryia; Alshaikh, Ahmed; Reuter, Dirk; Heyn, Christian (Nanomaterials)
Site-controlled Ga droplets on AlGaAs substrates are fabricated using area-selective deposition of Ga through apertures in a mask during molecular beam epitaxy (MBE). The Ga droplets can be crystallized into GaAs quantum dots using a crystallization step under As flux. In order to model the complex process, including the masked deposition of the droplets and a reduction of their number during a thermal annealing step, a multiscale kinetic Monte Carlo (mkMC) simulation of self-assembled Ga droplet formation on AlGaAs is expanded for area-selective deposition. The simulation has only two free model parameters: the activation energy for surface diffusion and the activation energy for thermal escape of adatoms from a droplet. Simulated droplet numbers within the opening of the aperture agree quantitatively with the experimental results down to the perfect site-control, with one droplet per aperture. However, the model parameters are different compared to those of the self-assembled droplet growth. We attribute this to the presence of the mask in close proximity to the surface, which modifies the local process temperature and the As background. This approach also explains the dependence of the model parameters on the size of the aperture.
Keywords: General Materials Science; General Chemical Engineering

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Degenerate photons from a cryogenic spontaneous parametric down-conversion source - Lange, Nina Amelie; Schapeler, Timon; Höpker, Jan Philipp; Protte, Maximilian; Bartley, Tim (Physical Review A)

Dispersion control with integrated plasmonic metasurfaces - Geromel, René; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (CLEO: Fundamental Science 2023)
We present a miniaturized pulse shaping device that creates an arbitrary dispersion through the interaction of multiple metasurfaces on less than 2 mm 3 volume. For this, a metalens and a grating-metasurface between two silver mirrors are fabricated. The grating contains further phase information to achieve the device's pulse shaping functionality.

Telecom C-band photon emission from (In,Ga)As quantum dots generated by filling nanoholes in In0.52Al0.48As layers - Deutsch, D.; Buchholz, C.; Zolatanosha, V.; Jöns, K. D.; Reuter, D. (AIP Advances)
We present the fabrication of strain-free quantum dots in the In0.53Ga0.47As/In0.52Al0.48As-system lattice matched to InP, as future sources for single and entangled photons for long-haul fiber-based quantum communication in the optical C-band. We achieved these quantum dots by local droplet etching via InAl droplets in an In0.52Al0.48As layer and subsequent filling of the holes with In0.53Ga0.47As. Here, we present detailed investigations of the hole morphologies measured by atomic force microscopy. Statistical analysis of a set of nanoholes reveals a high degree of symmetry for nearly half of them when etched at optimized temperatures. Overgrowth with 50–150 nm In0.52Al0.48As increases their diameter and elongates the holes along the [01̄1]-direction. By systematically scanning the parameter space, we were able to fill the holes with In0.53Ga0.47As, and by capping the filled holes and performing photoluminescence measurements, we observe photoluminescence emission in the O-band up into the C-band depending on the filling height of the nanoholes.
Keywords: General Physics and Astronomy

„Die Prüfungen werden mich sicherlich nicht zu einer besseren Lehrkraft machen.“ Wie beurteilen Studierende Prüfungen und Feedback im Lehramtsstudium? - Vogelsang, Christoph; Janzen, Thomas; Meier, Jana; Wotschel, Philipp

Als Lehrkraft gut beraten? Entwicklung und Erprobung eines handlungsnahen Prüfungsformates zur Erfassung von Beratungskompetenz von Lehramtsstudierenden - Wotschel, Philipp; Vogelsang, Christoph; Janzen, Thomas; Meier, Jana

NeMo.bil - Dekarbonisierung des Verkehrs mithilfe von Leichtbau-Fahrzeugschwärmen - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas (WerkstoffPlus Auto 13. Fachtagung für neue Fahrzeug- und Werkstoffkonzepte)

Assessing pre-service EFL teachers’ feedback performance in role-play-based simulations - Janzen, Thomas; Wotschel, Philipp; Meier, Jana; Vogelsang, Christoph (EARLI 2023)